2003
DOI: 10.1093/oxfordjournals.rpd.a006218
|View full text |Cite
|
Sign up to set email alerts
|

Anomolies between radiological and chemical limits for uranium after inhalation by workers and the public

Abstract: Exposure limits for workers and the public are based on both chemical toxicity and radiation dose. As a consequence of the different procedures used in their calculation they are incompatible, and adherence to one limit may result in a serious breach of the other. This paper explores the background to these limits, the problems posed by their application and proposes how best to achieve compliance with both limits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The effects of EHBP have been determined (Ubios et al 1994;Hengé-Napoli et al 1999;Martinez et al 2000;Houpert et al 2001;Martinez et al 2003). We have also demonstrated that CBMIDA is effective in removing uranium in rats (Fukuda et al 2001).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…The effects of EHBP have been determined (Ubios et al 1994;Hengé-Napoli et al 1999;Martinez et al 2000;Houpert et al 2001;Martinez et al 2003). We have also demonstrated that CBMIDA is effective in removing uranium in rats (Fukuda et al 2001).…”
Section: Discussionmentioning
confidence: 83%
“…The toxic dose of depleted uranium has been examined in animals and humans (Hodge 1973;Hursh and Spoor 1973;Yulle 1973;Leggett 1989;Stradling et al 1997Stradling et al , 2003. Chelation therapy is a useful method to reduce the risk of toxicity by accelerating excretion of uranium from the body.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biokinetic behavior of several compounds of Th and U are well known (International Commission on Radiological Protection (ICRP) 1959, publication no. 2), but there is little data about the biokinetic behavior of Th and U associated to mineral crystal lattice (Dias da Cunha et al 2002;Wan et al 2006;Stradling et al 2003;Sutton and Burastero 2004;Chen et al 2005;Li et al 2007). While there are available several data about the effects of Th and U in the human body, there is very few data about Ta toxicity and these few studies are not conclusive.…”
Section: Introductionmentioning
confidence: 99%